Economic and financial instruments of forest management in the Czech Republic - Perunová, Michaela; Zimmermannová, Jarmila (Frontiers in Forests and Global Change, 2023)
The forest bioeconomy becomes a feature of a climate-neutral economic system, while effective financial support is crucial for sustainable forest management. The main goal of this paper is to explain the impact of economic and financial instruments on the development of the forestry sector in the Czech Republic in the period 2000-2020. For research objectives, the methods of literature review, data analysis, correlation analysis, and regression analysis were used. Several models were established and tested. This paper presents the forest land model (FOLM) and wood biomass production model (WBIOM). In the monitored period, there was an increase in forest land in hectares in the Czech Republic, which was positively influenced by environmental investments in biodiversity and negatively by subsidies from the Rural Development Programme and the price of European Union Allowance. Based on the FOLM model results, 100 million CZK (4.07 million EUR) of environmental investments in biodiversity would contribute to an increase of 228 hectares of forest land. Concerning wood biomass production in cubic meters, it was influenced positively by the whole mixture of economic and financial instruments, such as emission trading, environmental taxation, financial contributions for forest management, state financial obligations, and subsidies. Based on the WBIOM model results, an increase in the price of an emission allowance by 100 CZK /Mg -1 (approx. 4 EUR/ Mg -1 ) would increase wood biomass production by approximately 934,614 cubic meters. Generally, the economic and financial instruments in the Czech Republic have an environmental impact and can influence the forest bioeconomy, at least in the long-term period. Concerning the complex influence of the emission trading on the forestry sector in the Czech Republic, it is ambiguousin the case of forest land rather negative, and in the case of wood biomass production positive. Therefore, focusing on the policy recommendations, we should underline economic and financial instruments connected with positive motivation in the forestry sector, such as grant schemas, subsidies, and investments in biodiversity.